2013
DOI: 10.1007/s10499-013-9655-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and histological studies of the brook trout, Salvelinus fontinalis (Mitchill), and the Arctic char, S. alpinus (L.) hybrids

Abstract: Although brook trout and the Arctic char hybrids are able to reproduce, individuals with decreased fertility or even fish that are unable to produce any gametes have been also described. Abnormal gonadal development and disturbances in the gamete production in the char hybrid offspring may be triggered by the odd chromosome number and disturbances in their pairing during meiosis. To verify this hypothesis, cytogenetic examination and the gonadal histology analysis of the brook trout x Arctic char hybrids were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Unintentional hybridization between Arctic char and brook trout may affect stocking practices. Presume problems with sex determination in hybrids results in the development of intersexual specimens as it was described among the F 1 Arctic char x brook trout individuals from the Rutki strains (Ocalewicz et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Unintentional hybridization between Arctic char and brook trout may affect stocking practices. Presume problems with sex determination in hybrids results in the development of intersexual specimens as it was described among the F 1 Arctic char x brook trout individuals from the Rutki strains (Ocalewicz et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Unintentional hybridization between Arctic char and brook trout may affect stocking practices. Presume problems with sex determination in hybrids results in the development of intersexual specimens as it was described among the F 1 Arctic char x brook trout individuals from the Rutki strains (Ocalewicz et al, ). The observations made by Dumas et al () on the reciprocal Arctic char x brook trout hybrids confirms problems with sexual maturation of hybrid males where individuals with good spermiation and sperm quality were scarce when compared to the parental species.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…; Ocalewicz et al. ) none of the reciprocal nucleocytoplasmic charr hybrids was viable (Babiak et al. , present paper).…”
Section: Discussionmentioning
confidence: 68%
“…The failure of the other androgenetic experiments has been attributed to the incompatibility between the egg cytoplasm of one species and the sperm nucleus from another species (Babiak et al 2002). Although, brook charr 9 Arctic charr hybrids are viable and usually fertile (Gross et al 2004;Ocalewicz et al 2013b) none of the reciprocal nucleocytoplasmic charr hybrids was viable (Babiak et al 2002, present paper). This suggested that in the brook charr and the Arctic charr nucleocytoplasmic incompatibility is expressed when a nucleus comprising chromosomes of only one of these species is present in the cytoplasm of the other one.…”
Section: Discussionmentioning
confidence: 82%